Computer technology competencies perceived as needed by vocational and technical teachers in Malaysia - Saud, Muhammad Sukri (2005)
The purpose of the study was to explore and describe the perceived competencies, importance, and educational needs in computer technology among vocational and technical teachers in Malaysia. The study was also to investigate the relationship among the selected demographics characteristic of vocational and technical teachers in Malaysia with perceived computer technology educational needs. A survey was conducted. The population studied involved Malaysian full-time vocational and technical high school teachers (N=284) employed by the Ministry of Education, Malaysia, during the 2003-2004 academic year. Two hundred and eighty-four teachers from nine vocational and technical schools were selected to participate in this study. Data were gathered via a mailed questionnaire and the questionnaire consisted two parts that measured the teachers' perceived importance and competence, and demographic information on the sample. The study showed that over 50% of the Malaysian vocational and technical teachers had not had formal computer technology training. Only 63% of the Malaysian vocational and technical teachers had a bachelor's degree or higher. The lowest computer technology educational needs of Malaysia vocational and technical teachers were computer operating skills. Media communication and telecommunication were the top two areas of educational needs among the eight domains of computer technology. The educational needs increased when the computer technology skills were more complicated. Demographic characteristics such as age, gender, years of teaching, and having a computer at home had low to negligible relationships with computer technology educational needs. Teachers7 degree held and computer technology educational experiences had negligible to low relationship with educational needs.